2022
DOI: 10.3390/molecules27217307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Traditional Cooking and Sous Vide Heat Treatment, Cold Storage Time and Muscle on Physicochemical and Sensory Properties of Beef Meat

Abstract: Consumers are avoiding the consumption of highly processed foods, aware of the negative effects of the additives or high temperatures used on the biological value of the food. This causes an interest in ways of minimal processing or low-temperature cooking procedures. However, to achieve the desired organoleptic quality, it is necessary to know the relationship between the parameters of the treatments and the type of raw material. The purpose of this study was to investigate the complex effects of traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Meat hardness and tenderness are closely related to the heating conditions, especially in the temperature range of 60–70 °C, which is associated with the denaturation or hydrolysis of collagen proteins [ 35 ]. On the other hand, sous-vide cooking positively impacts the texture parameters [ 36 ]. Nevertheless, based on the data obtained in this study, although the sous-vide cooking technique resulted in some noticeable changes in gumminess, these variations could still be considered an acceptable texture range when referring to the sensory evaluation data discussed in the previous sections of this manuscript.…”
Section: Resultsmentioning
confidence: 99%
“…Meat hardness and tenderness are closely related to the heating conditions, especially in the temperature range of 60–70 °C, which is associated with the denaturation or hydrolysis of collagen proteins [ 35 ]. On the other hand, sous-vide cooking positively impacts the texture parameters [ 36 ]. Nevertheless, based on the data obtained in this study, although the sous-vide cooking technique resulted in some noticeable changes in gumminess, these variations could still be considered an acceptable texture range when referring to the sensory evaluation data discussed in the previous sections of this manuscript.…”
Section: Resultsmentioning
confidence: 99%
“…For flavor, texture, and off-flavor, the 60℃ and 65℃ samples were significantly higher than the 55℃ sample (p-value < 0.05). Gil et al (2022) reported that in sous-vide cooking on meat, 60℃ appeared positive effect on sensory evaluation through improving appearance, shear force, thermal loss, and texture profile. Texture is mainly affected by enzymatic denaturation of myosin and collagen and as shown in the results of texture profiles (SEM photograph, Fiber cross-sectional area, sarcomere length, cooking yield, and shear force) show similar relations along with sensory evaluation (Mortensen et al, 2012).…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…Additionally, steak is rich in various B-group vitamins (such as vitamin B 12 , B 6 , niacin) and minerals (including iron, zinc, selenium) [10]. It offers a rich taste and distinctive flavor with versatile cooking methods such as frying, roasting, braising, and boiling [11]. The palatability of meat plays a crucial role in consumer choice [11].…”
Section: Introductionmentioning
confidence: 99%
“…It offers a rich taste and distinctive flavor with versatile cooking methods such as frying, roasting, braising, and boiling [11]. The palatability of meat plays a crucial role in consumer choice [11]. Fried steak provides an enjoyable texture and taste experience [12], but it also has certain drawbacks to consider.…”
Section: Introductionmentioning
confidence: 99%